Total Hip Arthroplasty for Hip Fractures: 5-Year Follow-Up of Functional Outcomes in the Oldest Independent Old and Very Old Patients. (March 2014) - Monzón, Daniel Godoy; Iserson, Kenneth V.; Jauregui, José; Musso, Carlos; Piccaluga, Francisco; Buttaro, Martin
Introduction: This study aimed to determine the dislocation and reoperation rate, functional outcomes, and the survival rate of the unique subset of very old but lucid and independent patients with hip fractures following a total hip arthroplasty (THA) and geriatric team-coordinated perioperative care. Method: Between 2000 and 2006, previously independent ambulatory patients ≥80 years old presenting with an intracapsular hip fracture were given THAs under the care of an integrated orthopedic surgery–geriatric service. Their fracture-related complications, ambulation, mental status, and survival were followed for 5 to 11 years postinjury. Results: Five years postinjury, 57 (61.3%) patients of the original study group were living. In all, 3 (3.2%) patients had postoperative hip dislocations (and 2 patients had dislocation twice) and 2 reoperations were needed within the first postoperative month. There were no hip dislocations or reoperations after the first year. Radiographs obtained on 88% of the surviving patients at 5 years postoperatively showed that all remained unchanged from their immediate postoperative images. Nearly half of the patients were still able to ambulate as they did preoperatively and their mixed-model equation was statistically unchanged. Conclusion: This study of patients >80 years old with previously good functional status demonstrates that with appropriate surgical (best prosthesis, good operating technique, and regional anesthesia) and geriatric (pre- and postoperative assessments, close follow-up, medication adjustments, and fall-prevention instruction) care, they have few hip dislocations and reoperations, survive postfracture at least as long as their noninjured contemporaries, and continue to function and ambulate as they did prior to their injury.